2022
DOI: 10.52965/001c.33774
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport following distal femur osteotomy: a systematic review

Abstract: Introduction Distal femur osteotomies (DFOs) are well-accepted procedures in treating unicompartmental knee osteoarthritis associated with valgus malalignment. This study aims to investigate the Return to sport (RTS) after DFO. Materials and methods We conducted a systematic review of the literature according to the PRISMA guidelines, including all articles published in English, with no time limit, excluding double-level knee osteotomies. Results Five articles were included for an overall cohort of 76 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Return to sport after these procedures is not predictable, and many patients alter their activities to lower-impact activities. 8,20,24,37 In a meta-analysis by Krych et al, 20 only 76% of patients (mean age, 35 years) returned to sport at 1 to 2 years; however, sports and levels of return were not specified. Rupp et al 37 reported that, after double-level osteotomy, patients returned to sports but at a lower frequency and reduced number of sports and with a shift to low-impact sports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Return to sport after these procedures is not predictable, and many patients alter their activities to lower-impact activities. 8,20,24,37 In a meta-analysis by Krych et al, 20 only 76% of patients (mean age, 35 years) returned to sport at 1 to 2 years; however, sports and levels of return were not specified. Rupp et al 37 reported that, after double-level osteotomy, patients returned to sports but at a lower frequency and reduced number of sports and with a shift to low-impact sports.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes often report that they are unable to return to sporting activities for a minimum of 1 to 2 years after surgery, and many fail to return to the same level of sport. 1,4,8,24,37 Recent data demonstrate that athletes shift toward lower-impact sporting activities after osteotomy and cartilage repair procedures. 37 It is projected that 1 of every 4 adults in the United States will have arthritis by the year 2030.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is no existing evidence whether the lateral opening wedge or the medial closing wedge technique leads to better clinical outcome [25, 30, 50]. Although there are several publications which reported on comparable results after DFO and lateral unicompartimental knee arthroplasty [34] and encouraging results regarding sports activities [7], no reports of the influence of joint angles are available. In case of varus knees, the influence of oblique joint line after high tibial osteotomy on the shear forces is published [29].…”
Section: Introductionmentioning
confidence: 99%
“…The demand for the return to sports (RTS) after KO is increasing with 71% of patients undergoing HTO motivated to return to their original sport activity [31]. Reviews show that 86–87% of patients after DFO [1, 10], 92% after DLO [29], and 76–94% after HTO [18, 21, 31] can return to sports at their pre‐surgery level. However, there are evidence and also systematic reviews evaluating RTS after KO [1, 10, 18, 21, 29, 31], and no evidence comparing outcomes among DFO, DLO and HTO.…”
Section: Introductionmentioning
confidence: 99%